Does confidence matters in adopting digital banking services? A study on university students' perception - Low, Siu Ann; Ong, Zu Yi; Soon, Han Ning (2024)
This study aims to investigate the intention to adopt digital banking services among Malaysian university students. In order to collect the data for this study, questionnaires were given to 50 Malaysian university students by using convenience sampling in non-probability sampling. In this study, several tests have been used to analyse the data such as descriptive analysis, internal consistency reliability, discriminant validity, collinearity, and multiple linear regression by using PLS-SEM. The result of this study examines the five independent variables which are performance expectancy, effort expectancy, social influence, facilitating conditions, and perceived trust. Then, the results show that performance expectancy has a significant influence on the intention to adopt digital banking services while the remaining independent variables which are effort expectancy, social influence, facilitating conditions, and perceived trust have an insignificant relationship with the intention to adopt digital banking services. Therefore, it is important to provide useful information to the academic sectors, industry, and government to focus when they make policy to enhance the intention to adopt digital banking services. Keywords: Intention to Adopt Digital Banking Services, Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Perceived Trust.